Binder Molecular Weight, Concentration, and Flow Rate Optimization for ZnO Nanofiber Synthesis for Electronic Device Applications - Harshada Mhetre; Vikas Kaduskar; Prashant Chougule; Yogesh Chendake; Nithesh Naik; Pavan Hiremath; Ritesh Bhat (Engineering Proceedings)
This study explores the critical factors influencing the properties of zinc oxide nanofibers, which are crucial for their applications in optoelectronics, solar cells, and biomedicine. We specifically investigate the impact of binder molecular weight, binder concentration, and solution flow rate on fiber shape, spinning ability, and diameter. By electrospinning zinc acetate, polyvinylpyrrolidone, and dimethylformamide solutions, we demonstrate that the composition, rheological characteristics, and processing parameters significantly affect nanofiber characteristics. We achieved optimized fiber diameters ranging from 24 to 62 nanometers through meticulous parameter modification. Further analysis via FESEM, XRD, and EDS confirms the suitability of these nanofibers for electronic applications, highlighting their potential contributions to the mentioned fields.